Handywomen and Birthing in Rural Ireland, 1851–1955. Issue 1 (April 2016) - Breathnach, Ciara
Abstract : It is largely agreed among scholars of social history and history of medicine that the medicalisation of maternity was slow to evolve in Ireland as it was beleaguered by competing professional, denominational and political agendas. Such discourses have dominated Irish history of medicine and hindered the progress of the medicalisation debate. A notable feature of the birthing process in Ireland is that for centuries handywomen, or untrained midwives, played a crucial role yet they have not been subject to the attention of historians. This article traces references to them in Irish Folklore Commission (1935–71) manuscripts and places them in wider social contexts to contend that their slight representation was a result of medico‐legal awareness and a desire to protect the identity of women who, after 1918, were operating outside the law.